2010
DOI: 10.1186/1475-2840-9-13
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ gene C161T substitution alters lipid profile in Chinese patients with coronary artery disease and type 2 diabetes mellitus

Abstract: BackgroundPeroxisome proliferator-activated receptor γ (PPARγ) is a ligand-activated transcription factor, which regulates gene expression of the key proteins involved in lipid metabolism, vascular inflammation, and proliferation. PPARγ may contribute to attenuating atherogenesis and postangioplasty restenosis. PPARγ C161→T substitution is associated with a reduced risk of coronary artery disease (CAD). Whether or not the gene substitution alters the risk of CAD in type 2 diabetes mellitus (T2DM) patients rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 30 publications
5
29
1
1
Order By: Relevance
“…In agreement with these observations, several recent studies have shown the effects of the C161T polymorphism on lipid profile and apolipoprotein ratios [19,20,29,35]. Additionally, several other studies showed the associations of other polymorphisms of PPAR-γ with lipid parameters, such as TG, TC, LDL and HDL [36,37,38,39,40]. In particular, Zhou and colleagues showed that this polymorphism was associated with a higher HDL-C level and a lower blood glucose level in CAD patients [15,39].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In agreement with these observations, several recent studies have shown the effects of the C161T polymorphism on lipid profile and apolipoprotein ratios [19,20,29,35]. Additionally, several other studies showed the associations of other polymorphisms of PPAR-γ with lipid parameters, such as TG, TC, LDL and HDL [36,37,38,39,40]. In particular, Zhou and colleagues showed that this polymorphism was associated with a higher HDL-C level and a lower blood glucose level in CAD patients [15,39].…”
Section: Discussionsupporting
confidence: 74%
“…Zhou et al showed that this polymorphism was associated with decreased risk of CAD in Chinese Han population [15]. On the other hand, several other studies have reported inconsistent data [5,14,28,29]. In particular, Vats and colleagues showed the lack of association between the allelic and genotypic frequencies of cases and controls [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, positive effects of this SNP on the metabolic phenotype have been demonstrated earlier. It has been associated with a favorable lipid profile (24,33,53), and reduced risk of coronary artery disease (54) and severe atherogenesis (24).…”
Section: Discussionmentioning
confidence: 99%